In-silico evaluation of Fragransol B from Myristica dactyloides for anti-inflammatory potential - Kuppuru Mallikarjunaiah Marulasiddaswamy, Bettadapura Rameshgowda Nuthan&, Sunilkumar Channarayapatna-Ramesh, Shrisha Naik Bajpe&, Shailasree Sekhar, Kukkundoor Ramachandra Kini (Journal of Applied Pharmaceutical Science, 2021)
The objective of the present investigation was to uncover the drug-likeness and possible anti-inflammatory mechanism of Fragransol B, a lignan molecule isolated and characterized from Myristica dactyloides through in-silico analysis to assist in the future evaluation of the compound. A comprehensive analysis of the drug-like properties was carried out through physicochemical and ADME parameters using the SWISSADME tool. Targets and biological properties were predicated using SwissTargetPrediction and PASS online along with toxicity evaluated through ProTox-II for a variety of toxicity endpoints. Furthermore, the protein–ligand interaction of Fragransol B along with known standards was initially evaluated against targeted proinflammatory targets and enzymes to pinpoint its anti-inflammatory ability through in-silico molecular docking analysis. The results demonstrated that Fragransol B has drug-likeness and lead-likeness properties with specified ADMET parameters of an effective drug candidate with passive gastrointestinal absorption and blood–brain penetration. The maximum binding affinity exhibited by Fragransol B against all targets confirms the anti-inflammatory efficiency of the molecule and thus unveils the hidden molecular mechanism of the traditionally used medicinal plant M. dactyloides. The predicted targets also confirm the compound’s anti-inflammatory potential and provide an insight into its multi-target potential. The study sheds light on future work focused on the experimental synthesis and evaluation of in-silico activity.
Keywords: Fragransol B, Myristica dactyloides, ADME, molecular docking, anti-inflammatory